A Comparative Study on Women Perception and Condition In the Event of Natural Disaster and Migration: A Qualitative Study from Sindh – Pakistan Flood 2010 - Memon, Rizwan Ali (Center for Risk Management & Sustainability and RSF Press, 2021)
In this study, we want to compare previous and current perception and condition of migrant’s women after completing ten years of emigrant at their new residential. In province of Sindh, district Jamshoro tehsil Kotri our samples, the migrant’s families from Jacobabad, Shikarpur, Kashmore-Kandhkot, Qamber-Shahdadkot and Dadu districts were migrating to adjacent areas of Kotri during 2010 due to flood. Many of them returned back to their area when recovered but a significant number from them are permanently settled in adjacent areas of Kotri. Comparing their perception and condition, we use a new technique of comparative twin questions with conceded closed and open-ended characteristics, and a qualitatively 94 migrants’ women were interviewed. Results reveal high populated families are more motivated about their employment and health concerns and these facilities force them to settle permanently. Further study divulges that participation of migrants’ women in socio-eco and domestic decision-making process was recorded unchanged, due to resemblance of their previous and current life standards. Our results recommend that the state intervention for the purpose migrant’s processing of Passports, Computer National Identity Cards (CNICs), and issuance of Domicile and Permanent Residence Certificates (PRCs) from their current residential addresses. Their job of nature changed from agriculture to industrial that ultimately knocking the door of long-term opportunities. Hence, government should make friendly policies to facilitate migrants’ families, which is essential for development of any society.